Aurora kinase Ipl1 facilitates bilobed distribution of clustered kinetochores to ensure error‐free chromosome segregation in Candida albicans. Issue 2 (29th May 2019) - Varshney, Neha; Sanyal, Kaustuv
Summary: Candida albicans, an ascomycete, has an ability to switch to diverse morphological forms. While C. albicans is predominatly diploid, it can tolerate aneuploidy as a survival strategy under stress. Aurora kinase B homolog Ipl1 is a critical ploidy regulator that controls microtubule dynamics and chromosome segregation in Saccharomyces cerevisiae . In this study, we show that Ipl1 in C. albicans has a longer activation loop than that of the well‐studied ascomycete S. cerevisiae . Ipl1 localizes to the kinetochores during the G1/S phase and associates with the spindle during mitosis. Ipl1 regulates cell morphogenesis and is required for cell viability. Ipl1 monitors microtubule dynamics which is mediated by separation of spindle pole bodies. While Ipl1 is dispensable for maintaining structural integrity and clustering of kinetochores in C. albicans, it is required for the maintenance of bilobed distribution of clustered kinetochores along the mitotic spindle. Depletion of Ipl1 results in erroneous kinetochore‐microtubule attachments leading to aneuploidy due to which the organism can survive better in the presence of fluconazole. Taking together, we suggest that Ipl1 spatiotemporally ensures bilobed kinetochore distribution to facilitate bipolar spindle assembly crucial for ploidy maintenance in C. albicans . Abstract : Candida albicans is a budding yeast. Although primarily a commensal of humans, it may turn into a pathogen and can even tolerate high concentrations of antifungal drugs. We show that the evolutionarily conserved Aurora B kinase Ipl1 regulates ploidy of cells by maintaining microtubule dynamics and the bilobed organization of kinetochore clusters. Depletion of Ipl1 results in erroneous kinetochore‐microtubule attachments resulting in aneuploidy which helps the organism to survive better in the presence of antifungal drugs.